Rancang Bangun Alat Twist Pipa Hollow - Salma Binti Astsalisa; Mohamad Hakam; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
This research aims to create a tool that is able to twist the needs of a component of a sofa product. This problem arises because of the need for the process of twisting aluminum components 120mmx30mmx708mm in size. However, existing equipment products are only able to twist sizes less than 8mmx8mm. By using the Ulrich method, identification of tool requirements is carried out to make 3 alternative design concepts. The needs for the main specifications of the tool after an interview is that the dimensions of the tool must be less than 1m x 1.5m and the ability of the tool to twist 10 degrees. Then, best design considered based on the dimensions, operational, strength, assembly, and maintenance. The best concept chosen was 3rd concept which was made with Mild Steel ST42 material, then with a P100 &P102 toggle clamp, and a maximum torsion capability of 73 degrees. The trial got 95% success rate and an additional twist angle of 3 degrees must be added due to the springback properties of aluminum. The total budget for the cost of producing this tool is approximately Rp.8,552,500.